The added value of coupling anti-dsDNA and anti-chromatin antibodies in follow-up monitoring of systemic lupus erythematosus patients - Caroline Carlé; Françoise Fortenfant; Chloé Bost; Julie Belliere; Stanislas Faguer; Dominique Chauveau; Antoine Huart; David Ribes; Laurent Alric; Gregory Pugnet; Laurent Sailler; Yves Renaudineau (Journal of Translational Autoimmunity)
Objective: The autoimmune response to chromatin (Chr) or one of the nucleosome components (double stranded (ds)DNA and histones) is typically associated with the development of systemic lupus erythematosus (SLE). Related autoantibodies (Ab) are heterogeneous and, among them, anti-dsDNA Ab are part of the classification criteria and recommended for monitoring SLE with regards to lupus flares and therapy responses. However, anti-dsDNA Ab biomarker performances are weak; therefore, coupling anti-dsDNA with anti-Chr Ab can be proposed, which is the aim of this study. Methods: In this single center study from 2009 to 2024, 269 SLE patients with follow-up information were retrospectively selected from a population of 646 individuals, including 325 SLE patients, who tested positive for anti-dsDNA and/or anti-Chr Ab (Bioplex 2200™). Bio-clinical information during follow-up were assessed at several time points through medical records in order to explore associations between the anti-dsDNA/Chr Ab profile with disease presentation, and anti-dsDNA/Chr Ab fluctuations with disease activity using clinical SLEDAI-2K, flares requiring specific treatment, and the therapeutic response. Results: At inclusion in the follow-up analysis, corresponding to diagnosis (116/269, 43.1 %) or flare (153/269, 56.9 %), SLE patients were subdivided into three serological groups: the double positive dsDNA/Chr group (DP+, 190/269: 70.6 %), followed by the single positive Chr group (SP-C+, 42/269: 15.6 %), and the single positive dsDNA group (SP-D+, 37/269: 13.8 %). The DP + group, which presented important anti-dsDNA/Ab variations during follow-up, was at risk to develop lupus nephritis (56.8 % versus 2.4 % in SP-C+ and 29.7 % in SP-D+ groups, p < 0.04) and serositis (30 % versus 9.5 % in SP-C+ group, p = 0.006). During follow-up, anti-dsDNA and Chr Ab levels in the SP-C+ and SP-D+ groups remained stable over time irrespective of disease activity, flares, and therapeutic response. Regarding the DP + group, disease activity was correlated with both anti-dsDNA (RmCorr = 0.46, p = 1.6x110-91) and anti-Chr (RmCorr = 0.38, p = 2.8x10-60) Ab levels, which can be used to predict flares. Following therapy introduction, Ab reduction occurred in all patients from the DP + group with a more pronounced effect reported in complete responders. Conclusion: coupling anti-dsDNA with anti-Chr Ab detection at disease initiation/flare allows definition of endotypes, which is useful to follow disease activity, predict lupus nephritis/serositis, and anticipate therapeutic response in the DP + group.